Single-element spark plasma sintering of silicon germanium. Issue 6 (1st November 2012) - Thompson, Daniel; Tritt, T. M.; Hitchcock, Dale; Lahwal, Ali
Abstract : Various compositions of the thermoelectric material, silicon germanium (SiGe), were synthesized directly from single elements (SE) via the spark plasma sintering (SPS) process. Through proper choice of commercially available powders, sintering conditions and stoichiometry, n-type and p-type samples with thermoelectric properties comparable with those of the Si80Ge20 alloys used in radioisotope thermoelectric generators for space missions were generated using the SE SPS process. The SE SPS technique is a rapid process requiring only 1 h to synthesize the desired material. This new synthesis technique is a viable alternative to traditional synthesis methods and provides the potential to discover novel avenues for improving the thermoelectric dimensionless figure of merit of SiGe alloys.